Pengembangan Media Pembelajaran Scrapbook Berbasis Gambar Seri pada Materi Macam-Macam Norma dalam Kehidupanku untuk Peserta Didik Kelas V SDN Tisnogambar 02 Jember - Aprilia Enggar Ratnasari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research is motivated by the problem of limited variation in learning media and its inability to attract students interest and active participation. Learning activities are still predominantly conducted using the lecture method without being supported by engaging visual media, causing students to have difficulty understanding the material, especially on the topic of norms in the Pancasila Education subject. As a result, the learning outcomes of students in classes VA and VB at SDN Tisnogambar 02 Jember have not met the minimum completion criteria. This aims of this research is to develop a scrapbook learning media based serial picture the material of various norms in my life, and to examine its validity, effectiveness, and practicality. The development model applied is Borg and Gall. Data collection methods include observation, interviews, expert validation, tests, questionnaires, and documentation. The media validation results showed a score of 96,1 (very feasible). The effectiveness test was conducted using an experimental method and analyzed with an independent sample t-test, yielding tcount of 6,455 > ttable 2,009 at a significance level 0,05, and a relative effectiveness of 68,71% (high effectiveness). The practicality test obtained a score of 93,30 (very practical). It can be concluded that the scrapbook learning media based serial picture on the material of various norms in m
Entry oleh Arif 2026 Maret 25
Keywords: Learning Outcomes; Scrapbook Learning Media; & Serial Picture